Antitumor effects of cationic synthetic peptides derived from Lys49 phospholipase A2 homologues of snake venoms - Araya Castillo, Cindy (2007)
The effects of two cationic synthetic peptides, derived from the C-terminal region of Lys49 phospholipase A2 homologues from snake venoms, upon various murine tumor cell lines (B16 melanoma, EMT6 mammary carcinoma, S-180 sarcoma, P3X myeloma, tEnd endothelial cells) were evaluated. The peptides are 13-mers derived from Agkistrodon piscivorus piscivorus Lys49 PLA2 (p-AppK: KKYKAYFKLKCKK) and Bothrops asper Lys49 myotoxin II (pEM-2[D]: KKWRWWLKALAKK), respectively, in the latter case with slight modifications and with all-D amino acids. All tumor cells tested were susceptible to the lytic action of the peptides. The susceptibility of tumor cell lines was not higher than that of C2C12 skeletal muscle myoblasts, utilized as a non-transformed cell line control. However, in a murine model of subcutaneous solid tumor growth of EMT6 mammary carcinoma, the intraperitoneal administration of pEM-2[D] caused a tumor mass reduction of 36% ( p < 0.05), which was of similar magnitude to that achieved by the administration of paclitaxel, an antitumor drug in clinical use. Thus, the C-terminal peptides of Lys49 phospholipase A2 homologues present antitumor effects that might be of interest in developing therapeutic strategies against cancer.